Right fronto-temporal activation differs between Chinese first-episode and recurrent Major Depression Disorders during a verbal fluency task: A near-infrared spectroscopy study. (30th June 2017) - Wang, Jiuju; Lv, Bin; Quan, Wenxiang; Wydell, Taeko N.; Tian, Ju; Wang, Pengfei; Liu, Jin; Dong, Wentian
Highlights: Recurrent MDD had lower activation on right prefrontal cortex than first-episode MDD. Recurrent MDD only activated significantly left prefrontal and superior temporal cortex. Recurrent MDD had lower activation on right prefrontal cortex than first-episode MDD.